Nonconjugated diene homopolymerization and copolymerization with ethylene catalyzed by α‐diimine Ni(II) complex/Et2AlCl. Issue 11 (13th March 2017) - Song, Shaofei; Wu, Anyang; Yu, Yan; Yang, Pengjia; Fu, Zhisheng; Fan, Zhiqiang
ABSTRACT: Four nonconjugated diene comonomers 1, 9‐decadiene (19DD), 6‐ethylundeca‐1, 10‐diene (EUD), 1, 5‐cyclooctadiene (COD) and cinene (1‐methyl‐4‐(prop‐1‐en‐2‐yl) cyclohex‐1‐ene) (CE) were used in copolymerization with ethylene catalyzed by α‐diimine Ni(II) complex ([2, 6‐(iPr)2 C6 H3 N = C(CH3 )−(CH3 )C = N2, 6‐(iPr)2 C6 H3 )]NiBr2 (1 )) activated by Et2 AlCl. These dienes showed quite distinct copolymerization behaviors. Ethylene‐19DD copolymerization formed highly branched polyethylene with cyclic units and pendent vinyls, and a large part of crosslinked polymer when the 19DD concentration was relatively high. Using EUD as comonomer lead to evidently reduced gel formation and increased content of pendent vinyl. COD can be incorporated in the copolymer with evidently lower catalyst efficiency than the ethylene homopolymerization, and CE behaves like an inert compound as it was not incorporated in the copolymer. Homopolymerization of 19DD with the same catalyst produced polymer containing both cyclic units and pendent vinyls. The cyclic units were formed by cyclopolymerization of the inserted 19DD after several steps of chain walking. Crosslinking through the pendent vinyl took place when the initial 19DD concentration was relatively high, forming large amount of gel in the product. © 2017 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem.2017, 55, 1900–1909 Abstract : Four nonconjugated diene comonomers—1, 9‐decadiene (19DD), 6‐ethylundeca‐ 1, 10‐diene (EUD), 1, 5‐cyclooctadiene (COD) and cinene (1‐methyl‐4‐(prop‐1‐en‐2‐yl) cyclohex‐1‐ene) (CE)—were used in copolymerization with ethylene catalyzed by α‐diimine Ni(II) complex [2, 6‐(iPr)2 C6 H3 N = C(CH3 )−(CH3 )C = N2, 6‐(iPr)2 C6 H3 )]NiBr2 activated by Et2 AlCl. Using EUD as comonomer lead to evidently reduced gel formation and increased content of pendent vinyl. Homopolymerization of 19DD with the same catalyst produced polymer containing both cyclic units and pendent vinyls.